Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Loyalitas Karyawan PT. BSI KC Medan S Parman dengan Kepuasan Kerja Sebagai Variabel Intervening - Safrida Safrida; Muhammad Yafiz; Fauzi Arif Lubis (ITB AAS INDONESIA Surakarta, 2023)
To increase employee loyalty and job satisfaction, companies need to pay attention to aspects of compensation and the work environment of employees to achieve company goals; if these aspects are fulfilled, it is effortless for companies to achieve company targets. This study aims to determine the effect of compensation and work environment on employee loyalty through job satisfaction as an intervening variable. The type of research used is quantitative research with an associative approach. Data collection techniques using questionnaires as the primary data collection tool. The population in this study is as many as 31 respondents who are employees of PT. Bank Syariah Indonesia S Parman Branch Office using a saturated sampling technique. Data were analyzed using the Path Analysis method, processing using SPSS 26.0. The results showed that partial compensation does not affect employee loyalty and job satisfaction because other variables also control compensation variables. Still, correlational payment has a significant influence on employee loyalty. Meanwhile, the work environment substantially affects employee loyalty and job satisfaction. And when the variables of compensation and work environment are through the variables of job satisfaction, these two variables do not affect employee loyalty. In contrast, job satisfaction has a significant influence on employee loyalty..